A Novel Probable Pathogenic PSEN2 Mutation p.Phe369Ser Associated With Early-Onset Alzheimer's Disease in a Chinese Han Family: A Case Report - Wan, Ke; Ma, Zhen-Juan; Zhou, Xia; Zhang, Yi-Mei; Yu, Xian-Feng; You, Meng-Zhe; Huang, Chao-Juan; Zhang, Wei; Sun, Zhong-Wu (Frontiers in Aging Neuroscience, 2021)
The pathogenesis of Alzheimer's disease is complex, and the early-onset Alzheimer’s disease (EOAD) is mostly influenced by genetic factors. Presenilin-1, presenilin-2 (PSEN2), and amyloid precursor protein are currently known as the three main causative genes for autosomal dominant EOAD, with the PSEN2 mutation being the rarest. In this study, we reported a 56-year-old Chinese Han proband who presented with prominent progressive amnesia, aphasia, executive function impairment and depression 5 years ago. The three-year follow-up showed that the patient experienced progressive brain atrophy displayed on magnetic resonance imaging (MRI) and dramatic cognitive decline assessed by neuropsychological evaluation. This patient was clinically diagnosed as EOAD based on established criteria. A heterozygous variant (NM_000447.2: c.1106T>C) of PSEN2 was identified for the first time in this patient and her two daughters. This mutation causing a novel missense mutation (p.Phe369Ser) in transmembrane domain 7 encoded by exon 11 had not been reported previously in 1000Genomes, ExAC or ClinVar databases. This mutation was predicted by four in silico prediction programs, which all strongly suggested that it was damaging. Our results suggest that this novel PSEN2 Phe369Ser mutation may alter PSEN2 protein function and associate with EOAD.